In Search of the Truth: Uncovering Nursing's Involvement in Colonial Harms and Assimilative Policies Five Years Post Truth and Reconciliation Commission - Paisly Michele Symenuk; Dawn Tisdale; Danielle H. Bourque Bearskin; Tessa Munro (York University Libraries, 2020)
The year 2020 marks five years since the Truth and Reconciliation Commission (TRC) of Canada released its Calls to Action, directing nursing to take action on both "truth" and "reconciliation." The aim of this article is to examine how nurses have responded to the TRC's call for truth in uncovering nursing's involvement in past and present colonial harms that continue to negatively impact Indigenous people. A narrative review was used to broadly examine nurses' responses to uncovering nursing's complicity in five colonial harms: Indian hospitals, Indian Residential Schools, child apprehension, Missing and Murdered Indigenous Women and Girls (MMIWG), and forced sterilization. The paucity of results during the post-TRC period demonstrates a lack of scholarship in uncovering the truth of nursing's complicity in these systems. Based on findings, we explore two potential barriers in undertaking this work in nursing, including a challenge to the image of nursing and anti-Indigenous racism.